If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (0.5x + -4) + -1(1.5x + 2.3) = 0 Reorder the terms: (-4 + 0.5x) + -1(1.5x + 2.3) = 0 Remove parenthesis around (-4 + 0.5x) -4 + 0.5x + -1(1.5x + 2.3) = 0 Reorder the terms: -4 + 0.5x + -1(2.3 + 1.5x) = 0 -4 + 0.5x + (2.3 * -1 + 1.5x * -1) = 0 -4 + 0.5x + (-2.3 + -1.5x) = 0 Reorder the terms: -4 + -2.3 + 0.5x + -1.5x = 0 Combine like terms: -4 + -2.3 = -6.3 -6.3 + 0.5x + -1.5x = 0 Combine like terms: 0.5x + -1.5x = -1x -6.3 + -1x = 0 Solving -6.3 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6.3' to each side of the equation. -6.3 + 6.3 + -1x = 0 + 6.3 Combine like terms: -6.3 + 6.3 = 0.0 0.0 + -1x = 0 + 6.3 -1x = 0 + 6.3 Combine like terms: 0 + 6.3 = 6.3 -1x = 6.3 Divide each side by '-1'. x = -6.3 Simplifying x = -6.3
| 19x-8=12x-43 | | 12(4+n)+5(-2n-9)=1 | | 5a+8-4=-21 | | 116=-4x+2(-5x-5) | | 12x^2-96x+0=0 | | 13x=-7x+6*5 | | 110+.60x=70+.80x | | 4xy^3*7x^2y^3= | | 3(-4-2)-7=-85 | | 5+12=2z | | 17=9x+5-x | | x=60+0.50*125 | | 5x-mx=w | | 5x-7=1x-4 | | 2x/5-4=7x-8 | | 12x^2-96x=0 | | -3f+3(-3f+5)= | | -3-21x=-8x-8 | | 64-32x=80 | | 55=6a-7 | | 2xy+2x=55 | | 7x^2+4x-40=0 | | .5x+1.8=-.7 | | 6a-12=42+5z | | 2sec^2x=3tan^2x+1 | | 0.25(5x-4.2)+0.75(4.4x-1.25)= | | 2+2r=-2(7r-1) | | 4x+6=4x+7 | | 10x+2y+.10z=120 | | X-7+(7)=12+(7) | | 7n^2+4n-40=0 | | -2z-19=z-10 |